2019
DOI: 10.1002/bin.1672
|View full text |Cite
|
Sign up to set email alerts
|

Examining extinction bursts in the treatment of pediatric food refusal

Abstract: Escape extinction has been shown to be highly effective in the treatment of food refusal; however, unpleasant side effects such as extinction bursts may accompany extinction procedures. Bursting has been reported to occur in 24% to 39% of all cases for which extinction was used as a component during treatment of problem behavior. Although commonly used in treatments, the occurrence of extinction bursts in the treatment of pediatric food refusal has not been studied. This study measured the frequency of burstin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…On a session‐wide level, none of the eight rats showed an increase in response rate following the implementation of extinction within‐session, regardless of whether reinforcement consumption time was included in response rate calculations or not and regardless of whether baseline mean or maximum response rates were used as the relevant comparison. As in previous studies, we saw more evidence of an extinction burst when responding during only the first minute following the transition to extinction was considered (Katz & Lattal, 2020; Lattal et al, 2020; Woods & Borrero, 2019). Our analyses also compared the difference between within‐session analyses when calculated with or without reinforcer consumption time included and showed that inclusion of this time in baseline response rate calculations can increase the apparent prevalence of an extinction burst in the first minute of exposure to extinction.…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…On a session‐wide level, none of the eight rats showed an increase in response rate following the implementation of extinction within‐session, regardless of whether reinforcement consumption time was included in response rate calculations or not and regardless of whether baseline mean or maximum response rates were used as the relevant comparison. As in previous studies, we saw more evidence of an extinction burst when responding during only the first minute following the transition to extinction was considered (Katz & Lattal, 2020; Lattal et al, 2020; Woods & Borrero, 2019). Our analyses also compared the difference between within‐session analyses when calculated with or without reinforcer consumption time included and showed that inclusion of this time in baseline response rate calculations can increase the apparent prevalence of an extinction burst in the first minute of exposure to extinction.…”
Section: Methodssupporting
confidence: 79%
“…Finally, when reinforcement time was included in rate calculations, the prevalence of the extinction burst was always greater than when it was excluded from such calculations. Overall, these findings correspond with previous research suggesting that the extinction burst is likely to be most apparent based on samples of time smaller than an entire session (e.g., Donny et al, 1995;Harris et al, 2007;Katz & Lattal., 2020;Lattal et al, 2020;Pushparaj et al, 2012;Salamone et al, 1995;Schramm-Sapyta et al, 2006;Woods & Borrero, 2019). Thus, when it occurs, the extinction burst appears to be a relatively short-lived phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, the child learns that if he or she does not quickly accept what is presented or tries to push it away, it will not be removed and positive reinforcement will not be delivered. Extinction procedures are commonly associated with undesirable side effects such as extinction bursts; however, Woods and Borrero (2019) concluded that extinction bursts occurred for a small portion of children during escape extinction treatment for feeding problems (30%). Nevertheless, escape extinction to treat feeding problems may not be appropriate in typical settings and should be implemented by highly trained staff to ensure high integrity (Bachmeyer, 2009) 2 Case Introduction…”
mentioning
confidence: 99%